The Phenomenon of Worship: Seven Principles of Designing Prayer Room at Home - Putra, Hadi Jaya; Kusuma, Hanson Endra; Sabatini, Stefani Natalia; Dwika Aprilian, Rizki (EMARA: Indonesian Journal of Architecture, 2022)
Worship is essential to every human being, but finding a house with a particular prayer room is still rare. This study seeks to capture the various phenomena of worship in the dwelling, consisting of intrinsic and extrinsic motivation. In general, the choice of space for prayer at home stems from intrinsic motivation from within. This research seeks to find extrinsic motivation, a characteristic of the environment that is then analyzed and compiled into design principles. This research was conducted using a qualitative grounded theory approach. The data were collected by distributing open questionnaires freely (non-random sampling). The data obtained from 192 respondents were analyzed using content analysis, which was carried out in three stages: open coding, axial coding, and selective coding. The investigation found seven (seven) designs for unique prayer rooms in the house. These principles include comfort, privacy, tranquility, minimal distraction, flexibility, cleanliness, and closeness. This study also revealed that a particular room for worship could increase religious activities at home and interaction between family members in spiritual and religious aspects